Target-organ damage and incident hypertension: the Korean genome and epidemiology study. Issue 3 (March 2016) - Kim, Seong Hwan; Kim, Yong-Hyun; Kim, Jin-Seok; Lim, Sang Yup; Jung, Jae Hyun; Lim, Hong Euy; Kim, Eung-Ju; Cho, Goo-Yeong; Baik, Inkyung; Sung, Ki-Chul; Park, Juri; Lee, Seung Ku; et al.
Abstract : Objective: Hypertension is associated with cardiovascular organ damage. However, data are scanty on whether individual forms or combinations of subclinical target organ damage (TOD) increase the risk of incident hypertension in nonhypertensive study participants. Methods: A total of 1785 nonhypertensive participants from the fourth biennial examination (2007–2008) of the Korean Genome and Epidemiology Study were followed-up for four years. Echocardiographic left ventricular (LV) hypertrophy, LV diastolic dysfunction, increased carotid intima–media thickness (cIMT), and brachial-ankle pulse wave velocity (baPWV) were defined according to the current guidelines. Results: During 4-year follow-up, 19.9% of participants developed hypertension. In multivariate Cox proportional hazards models, the adjusted hazard ratios for developing hypertension were 1.39, 1.66, 1.48, and 0.78 for higher values of the LV mass index, cIMT, baPWV, and tissue Doppler e′ velocity, respectively (all P  < 0.01). The hazard ratios for LV hypertrophy, LV diastolic dysfunction, cIMT >75th percentile, and baPWV ≥ 1400 cm/s were 1.61, 1.30, 1.86, and 2.07, respectively (all P  < 0.05). Compared with participants without any TOD, those with combinations of TOD types had significantly greater risk for developing hypertension (hazard ratio = 2.12 and 3.98 for 1-2 and 3-4 TOD sites, respectively, all P  < 0.001). Conclusion: In the nonhypertensive population, each subclinical form of TOD independently predicts incident hypertension. In addition, the combinations of various forms of TOD are associated with stepwise increases in the risk for developing hypertension. The results suggest that asymptomatic TOD does not always exist in an intermediate stage in the cardiovascular continuum. Abstract : Supplemental Digital Content is available in the text